Formulation Design and in vitro Evaluation of Orodispersible Tablets of Orlistat by Direct Compression Method - Wajid, Syed (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: The objective of the study was to formulate and evaluate orally disintegrating tablet of orlistat. Materials and Methods: Direct compression method was used to formulate orally disintegrating tablet of orlistat by employing different superdisintegrants, entragit, and magnesium stearate (lubricant), Talc. These prepared formulations were then evaluated using pharmacopeia and non-pharmacopeia methods. Dissolution and assay tests were performed using USP apparatus II and ultraviolet spectrophotometry, respectively. Results: All formulations showed compliance with pharmacopeial standards. The effect of superdisintegrants concentration and direct compression method on drug release profile was studied. Release profile of F12 which contains 2% of Ac-di-sol in combination with entragit, were found to be satisfactory comparing to other formulations. Conclusion: Formulation prepared with Ac-di-sol in combination with entragit (F12), as processed excipient was found to be the best superdisintegrants for the preparation of orlistat orally disintegrating tablets formulations. Due to it has exhibited faster disintegration time and best dissolution profile when compared to other formulations.